23 things they don't tell you about capitalism - Chang, Ha-Joon. (London : Penguin Books, 2011)
Challenges popular misconceptions while making startling revelations about free-market practices, explaining the author's views on global capitalism dynamics while making recommendations for reshaping capitalism to humane ends.
There is no such thing as a free market -- Companies should not be run in the interest of their owners -- Most people in rich countries are paid more than they should be -- The washing machine has changed the World more than the Internet has -- Assume the worst about people and you get the worst -- Greater macroeconomic stability has not made the world economy more stable -- Free-market policies rarely make poor countries rich -- Capital has a nationality -- We do not live in a post-industrial age -- The US does not have the highest living standard in the world -- Africa is not destined for underdevelopment -- Governments can pick winners -- Making rich people richer doesn't make the rest of us richer -- US managers are over-priced -- People in poor countries are more entrepreneurial than people in rich countries -- We are not smart enough to leave things to the market -- More education in itself is not going to make a country richer -- What is good for General Motors is not necessarily good for the United States -- Despite the fall of communism, we are still living in planned economies -- Equality of opportunity may not be fair -- Big government makes people more open to change -- Financial markets need to become less, not more, efficient -- Good economic policy does not require good economists -- Conclusion: How to rebuild the world economy.
"First published in Great Britain in 2010 by Allen Lane"--T.p. verso.
Includes bibliographical references (pages [265]-276) and index.
Donated By Akbar Ali Khan
Keywords: Capitalism; Economic policy; Free trade; Capitalism; Free trade; Economics